Diffusion and sorption of sulfur mustard and bis(2-chloroethyl)ether in elastomers: A comparative study - Dubey, Vinita; Gupta, A. K.; Maiti, S. N.; Rao, N. B. S. N. (Wiley, 2000)
Bis(2-chloroethyl)ether, a nonvesicant and easy to handle chemical, was proposed as a model compound for the vesicant sulfur mustard (SM) in routine permeation testing of protective devices. The proposition was based on detailed studies on sorption of these chemicals in elastomers. From the sorption plots and permeation parameters, it was found that the model compound diffuses faster than SM, and the diffusion follows Fickian kinetics. Free volume models, such as those developed by Lee and Salame, together with solubility and thermodynamic interaction parameters, validated the observed sorption phenomenon and afforded a criterion for predicting the barrier properties of elastomers